e-Procurement adoption by suppliers: Enablers, barriers and critical sucess factors - Andrade, P.; Alturas, B. (Proceedings of the International Conference on e-Business - ICE-B (ICETE 2009), 2009)
This paper presents a current research with the aim to identify the enablers, barriers and critical success factors for e-procurement adoption by suppliers. Any successful e-procurement system needs suppliers disposed to trade electronically. We present a review of the actual literature about e-Procurement, with focus on the barriers, enabler´s and CSF´s already identified. A research methodology is proposed to study the problem, and this work will contribute to better address the issues faced by suppliers on e-procurement implementations.